2021
DOI: 10.3390/ijms22031248
|View full text |Cite
|
Sign up to set email alerts
|

Integrating LCM-Based Spatio-Temporal Transcriptomics Uncovers Conceptus and Endometrial Luminal Epithelium Communication that Coordinates the Conceptus Attachment in Pigs

Abstract: Attachment of conceptus to the endometrial luminal epithelium (LE) is a critical event for early placentation in Eutheria. Since the attachment occurs at a particular site within the uterus, a coordinated communication between three spatially distinct compartments (conceptus and endometrial LE from two anatomical regions of the uterus to which conceptus attaches and does not attach) is essential but remains to be fully characterized. Using the laser capture microdissection (LCM) technique, we firstly developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…Results showed that Chi-miR-451-5p was mainly expressed in the stromal cells of the endometrium, suggesting that stromal cells may play a role in the secretion of chi-miR-451-5p. Additionally, higher chi-miR-451-5p levels were detected in the endometrial luminal epithelium on P16, as communication between the endometrial luminal epithelium and embryo is important for embryo implantation [ 76 ]. Moreover, the dual-luciferase reporter assay proved that chi-miR-451-5p directly targets 3′-UTR of PSMB8 .…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that Chi-miR-451-5p was mainly expressed in the stromal cells of the endometrium, suggesting that stromal cells may play a role in the secretion of chi-miR-451-5p. Additionally, higher chi-miR-451-5p levels were detected in the endometrial luminal epithelium on P16, as communication between the endometrial luminal epithelium and embryo is important for embryo implantation [ 76 ]. Moreover, the dual-luciferase reporter assay proved that chi-miR-451-5p directly targets 3′-UTR of PSMB8 .…”
Section: Discussionmentioning
confidence: 99%
“…Sample collection was carried out according to Wang et al 6 Briefly, Yorkshire gilts were mated to Yorkshire boars at the onset of the second estrus (Day 0) and again 12 h later. On gestational days 12, 15, and 18, the uterus was taken from each gilt and cut into segments (3–4 gilts/gestational day).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence assays were carried out as described by Wang et al 6 The primary antibodies used were ST6GAL1 (1:50, ab77676, abcam), ST6GAL2 (1:50, AF7747; R&D Systems), E‐cadherin (1:50, ab40772; abcam), β‐catenin (1:50, ab6302; abcam), Vimentin (1:50; sc‐73258), Rac1 (1:30, 66122–1‐Ig; Proteintech) and RhoA (1:50, 10749–1‐Ig; Proteintech). The fluorescent‐dye conjugated secondary antibodies used were Alexa Fluor ® 488 (1:100, ab150077/ab150113; abcam) or Alexa Fluor ® 555 (1:100, A21422/A21428; invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these studies were unable to accurately capture cell-type-specific gene expression changes. Recently, laser capture microdissection (LCM) has been applied to obtain the global gene expression profiles in luminal epithelial cells, glandular epithelial cells and stromal cells of peri-implantation porcine endometrium ( Zeng et al, 2018 ; Zeng et al, 2019 ; Wang et al, 2021 ). The limitation of LCM-based methods is that cell types such as various immune cells can be hardly isolated.…”
Section: Introductionmentioning
confidence: 99%